Feasibility Study to Connect All African Higher Education Institutions to High-Speed Internet : Burkina Faso Case Study - World Bank (World Bank, Washington, DC, 2021)
Burkina Faso considers the education sector a critical player in its development priorities. The higher education sector, which comprised 18 accredited universities (10 public and 8 private) and 75 Grandes Ecoles (23 public and 52 private) in 2020, is expected to play an important role in education and training to support the country’s priority education outcomes by 2030. Digital technologies provide opportunities for addressing the challenges facing higher education - growing demand for higher education, falling quality, the mismatch between education and employability and disconnection between research and development challenges. Higher education institutions (HEIs) in Burkina Faso lack adequate bandwidth to meet their research and education needs because the available broadband is expensive and insufficient to address their needs. As part of the digital economy for Africa (DE4A) initiative, the World Bank commissioned a study to develop an operational roadmap to connect all African HEIs to high-speed Internet. As part of the feasibility study, this report provides a detailed country-level assessment to connect all HEIs in Burkina Faso to high-speed Internet. Chapter one is introduction, the report provides a country overview in chapter two to provide the national context. The connectivity gap has both a supply-side and a demand-side is chapter three explores the demand-side, focusing on information and communications technology (ICT) in the education sector and the challenges impacting the use of information and communication technologies for teaching, learning, and research - creating the pull factors; and chapter four examines the supply-side, the ICT sector’s key components and the challenges affecting high-speed connectivity. Chapter five presents a high-level summary of the status of national research and education network (NREN) as well as its achievements and limitation in delivering high-speed connectivity to HEIs. Drawing on findings from the earlier chapters, chapter six discusses the cost of connecting all HEIs in Burkina Faso to high-speed Internet. A summary is given in chapter seven, followed by the appendices.